Noninvasive MRI Monitoring of the Effect of Interventions on Endothelial Permeability in Murine Atherosclerosis Using an Albumin‐Binding Contrast Agent. Issue 5 (26th September 2013) - Phinikaridou, Alkystis; Andia, Marcelo E.; Passacquale, Gabriella; Ferro, Albert; Botnar, René M.
Abstract : Background: Endothelial dysfunction promotes atherosclerosis. We investigated whether in vivo magnetic resonance imaging (MRI) using an albumin‐binding contrast agent, gadofosveset, could monitor the efficacy of minocycline and ebselen in reducing endothelial permeability and atherosclerotic burden in the brachiocephalic artery of high‐fat diet (HFD)–fed ApoE −/− mice. Methods and Results: ApoE −/− mice were scanned 12 weeks after commencement of either a normal diet (controls) or an HFD. HFD‐fed ApoE −/− mice were either untreated or treated with minocycline or ebselen for 12 weeks. Delayed‐enhancement MRI and T1 mapping of the brachiocephalic artery, 30 minutes after injection of gadofosveset, showed increased vessel wall enhancement and relaxation rate (R1, s −1 ) in untreated HFD‐fed ApoE −/− mice (R1 =3.8±0.52 s −1 ) compared with controls (R1 =2.15±0.34 s −1, P <0.001). Conversely, minocycline‐treated (R1 =2.7±0.17 s −1, P <0.001) and ebselen‐treated (R1 =2.7±0.23 s −1, P <0.001) ApoE −/− mice showed less vessel wall enhancement compared with untreated HFD‐fed ApoE −/− mice. Mass spectroscopy showed a lower gadolinium concentration in the brachiocephalic artery of treated (minocycline=28.5±3 μmol/L, ebselen=32.4±4 μmol/L) compared with untreated HFD‐fed ApoE −/− mice (191±4.8 μmol/L) ( P <0.02). Both interventions resulted in a lower plaque burden as measured by delayed‐enhancement MRI (minocycline=0.14±0.02 mm 2, ebselen=0.20±0.09 mm 2, untreated=0.44±0.01 mm 2 ; P <0.001) and histology (minocycline=0.13±0.05 mm 2, ebselen=0.18±0.02 mm 2, untreated=0.32±0.04 mm 2 ; P <0.002). Endothelium cells displayed fewer structural changes and smaller gap junction width in treated compared with untreated animals as seen by electron microscopy (minocycline=42.3±8.4 nm, ebselen=56.5±17 nm, untreated=2400±39 nm; P <0.001). Tissue flow cytometry of the brachiocephalic artery showed lower monocyte/macrophage content in both ebselen‐ and minocycline‐treated mice (8.06±3.2% and 7.62±1.73%, respectively) compared with untreated animals (20.1±2.2%) ( P =0.03), with significant attenuation of the proinflammatory Ly6C high subtype (untreated mice, 42.64±6.1% of total monocytes; ebselen, 14.07±9.5% of total monocytes; minocycline, 26.42±0.6% of total monocytes). Conclusions: We demonstrate that contrast‐enhanced MRI with an albumin‐binding contrast agent can be used to noninvasively monitor the effect of interventions on endothelial permeability and plaque burden. Blood albumin leakage could be a surrogate marker for the in vivo evaluation of interventions that aim at restoring endothelial integrity.